Internationalism and the state in the twentieth century - Navari, Cornelia, 1941- (Routledge, 2000)
The major changes in state relations which have occurred during the present century are described in this book and the sources from which they emerged. It look at strategies and the choices of the major powers in the direction of internationalisation.